(3cJGH SDGd hLhGHs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s ((3SdjeGf Hf eMeO SMdhd GdEOdHi s)
(3ChdgG (B:s
(3cJGH ajg cjajg jJdbi Gdedc GdhMi ef Gddg JYGdi HcdGe jageg Gdedc CHh HYQHi Ch HYHQGfi Ch HTF jageg Gdedc hGdLhGH Yfg GdYdGeI GdLdGd GdSjhWi QMeg Gddg HSe Gddg GdQMef GdQMje eSCdI ai cjajI GdhMi ef Gddg JYGdi s
(3BNQgG (B:s
(3dG Edg EdG Gddg ef LedI cdeGJ GdbQBf aJaVjdgG Ydi Hbjg cdeGJg ef HGH JaVjd HYV GdbQBf Ydi HYV dG ef HGH ZjQ GdbQBf Ydi GdbQBf Je Pdc HMeO Gddg hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hSde JSdjekG cKjQkG Je s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV cdeGJgG HGdMeQIs
(3Ydi gGeT GdQSGdI HYV GdahGFO s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3GdJhMjO hGdedd hGdfMds